Umayyad Mosque in Aleppo yesterday, today and tomorrow - Alafandi, Rami; Abdul Rahim, Asiah (InternationalJournal.org, 2014)
The objective of this paper is to show the importance of the architectural and artistic heritage of Aleppo, particularly the Umayyad Mosque. Aleppo is the second largest city in Syria (after the capital Damascus) and is the commercial capital of Syria. Aleppo has a long history, extending from the third millennium BC to the Islamic era. The remains and monuments are evidence from those great civilizations. Many pieces of literature mention that the Amorites were the first inhabitants in Aleppo during the third millennium BC. In 223 BC, the Greek commander (SeleucusNikator) re-organized and planned the city. Later, Islamic rulers made Aleppo great by re-building its walls, gates, towers and citadel. The Muslims also built mosques, schools, inns, markets, hospitals, bathrooms, and public facilities. Consequently, Aleppo flourished and became a very important station for the Silk Road; the third largest city in the Ottoman Empire after Istanbul and Cairo. In 1986, UNESCO added Old Aleppo City to the World Heritage List. In 715 Umayyad Caliph Al- Walid built the Great Umayyad Mosque to demonstrate the development of Islamic art and architecture this time period. Until now the Umayyad Mosque has been considered one of Aleppo’s main city symbols. Since 2012 the much of Syria’s architectural heritage in have been destroyed due to internal war. In Aleppo the losses in both the ancient and modern parts of the city have been tremendous. The Umayyad Mosque has been particularly damaged and many massive parts destroyed such as the Minaret, the arcades, the main hall, and the courtyard. This paper will highlight some recommendations to protect and restore the Umayyad Mosque in Aleppo for future use.